Apakah Classification Shifting Memoderasi Pengaruh Good Corporate Governance terhadap Corporate Social Responsibility Pada Perusahaan Manufaktur yang Terdaftar di BEI? - Ina Mutmainah (Politeknik Negeri Batam, 2020)
This study aims to determine the effect of good corporate governance on CSR disclosure which is moderated by earning management. This study uses secondary data from manufacturing companies listed on the Indonesia Stock Exchange for 2014-2018 periods. The purposive sampling method was selected for data collection, then the data was analyzed by using the absolute difference of moderation test. The results of this study indicate that good corporate governance which consists of institutional ownership, and independent commissioners have no significant effect on CSR disclosure, while audit committees have a positive effect on CSR disclosure. Thoreover, this study earnings management strengthen the positive influence of the institutional ownership on CSR disclosure, and strengthen the negative influence of the audit committee on CSR disclosure. However, earning management fails to find moderation role of independent commissioners on CSR disclosure.